Training On Developing Electronic Learning Tools Integrated With Ethnoscience Using Heyzine For High School Teachers In Batang Hari Regency - Jufrida; Dani, Rahma; M. Furqon, M. Furqon; Kurniawan, Wawan; Riantoni, Cicyn (The Future of Education Journal, 2024)
In the context of the Independent Curriculum (Kurikulum Merdeka), emphasis is placed on integrating elements of local wisdom into the learning process to support the achievement of student profiles aligned with Pancasila principles. Therefore, teachers are expected to prepare instructional materials that incorporate elements of local wisdom in line with the Independent Curriculum. However, findings in the field, particularly in Batang Hari Regency, indicate that some schools, such as SMAN 2 Batang Hari, still rely on teaching materials based on the previous curriculum, which do not incorporate local wisdom or ethnoscience aspects. The purpose of this community service activity is to train teachers at SMAN 2 Batang Hari to develop Independent Curriculum learning tools that integrate local wisdom or ethnoscience aspects using Heyzine. This platform is utilized to create interactive digital learning modules based on ethnoscience, allowing teachers to visually and contextually present elements of Jambi’s local culture. The method used in this activity is a workshop comprising three stages: preparation, implementation, and evaluation. This training took place on August 29, 2024, at SMAN 2 Batang Hari. The results of this training indicate that teachers at SMAN 2 Batang Hari gained a good understanding of the concepts, techniques, and use of Heyzine in preparing learning tools in line with the Independent Curriculum, thereby enabling more effective integration of local wisdom or ethnoscience aspects into the learning process